An RFID-enabled distributed control and monitoring system for a manufacturing system - Barcnji, Ali Vatankhah; Vatankhah Barenji, Reza; Sefidgari, Bahram Lavi (My University, 2013)
Flexible manufacturing systems as complex and stochastic environments require the development of innovative, intelligent control architectures for supporting more flexibility, agility and re-configurability. Distributed manufacturing control system addresses this challenge by introducing an adaptive production control approach and is supported by the presence of autonomous control units which are cooperating with each other. The majority of the current distributed control systems, till now suffer from lack of flexibility and agility when the product verity is high or the product volume is low, and also there is not reconfigure in case of ad-hoc events. To overcome these limitations, a kind of drawback of an excessive dependence on up-to-date information about the products and other elements which move within the system is essential. To this end, RFID as a new emerging technology was introduced which uses radio-frequency waves to transfer data between a reader and movable item for identification, tracking and categorization purpose. This study discusses the architecture devised to deploy RFID-enabled distributed control and monitoring system by means of a set of agents that are responsible for the realization of different control and monitoring tasks and cooperating with each other to enhance agility, flexibility and re-configurability of manufacturing system. The RFID-enabled distributed control and monitoring system has been explored using a flexible manufacturing system (EMU-CIM lab) to demonstrate the feasibility of the proposed architecture successfully. © 2013 IEEE.
2013 3rd International Conference on Innovative Computing Technology, INTECH 2013 --
Keywords: Distributed control system; FMS; Multi-agent system; RFID-technology